Binuclear Complexes of Nickel(II) with the ligand 1,2,5,6-tetraphenyl-3,4-diaza-1,6-dihydrxyimino-2,4-hexadine - Sahu, K.; Kumar Sahu, Rajeev (Asian Journal of Chemistry, 2010)
Binuclear complexes of Ni(II) with the ligand 1,2,5,6-tetraphenyl-3,4-diaza-1,6-dihydroxyimino-2,4-hexadiene of the type Ni2L2X4 where X = Cl–, Br–, I– or NO3– have been isolated. Vibrational spectra suggest co-ordination of the ligand with the metal ions through the azine and oxime nitrogen atoms in a bi-bidentate manner. The complexes are suggested to possess a hydrogen bonded binuclear structure on the basis of IR data. Magnetic data and electronic spectra reveal a tetragonal crystal field around metal ions.